Training and Development Practices: A Comparative Study of Public and Private Sector Industries - Lokesha, M. U.; Siddegowda, Y. S. (Prabandhan: Indian Journal of Management, 2009)
India's economy is diverse and encompasses agriculture, handicrafts, textiles, manufacturing and a multitude of services. Although two thirds of the Indian workforce still earns their livelihood directly or indirectly through agriculture, industries and services are a growing sector and are playing an increasingly important role in India's economy. For a predominantly agricultural country like India, development of industries is a must. Industrial development alone can provide a secure basis for a rapid growth of income. The mass production technology opened up tremendous opportunities for development in allied areas, and gave decisive thrust to the economy. Today's competitive business environment is forcing an increasing number of organizations to find ways to improve leadership skills, competencies and capabilities of the entire workforce; because competent and motivated people can make things happen and enable an organization to achieve its goals. Therefore, organizations should continuously ensure that the dynamism, competency, motivation and effectiveness of the employees remain at high levels.